ITGB5 Plays a Key Role in Escherichia coli F4ac-Induced Diarrhea in Piglets - Wang, Wenwen; Liu, Yang; Tang, Hui; Yu, Ying; Zhang, Qin (Frontiers in Immunology, 2019)
Enterotoxigenic Escherichia coli (ETEC) that express F4ac fimbriae are the major pathogenic microorganism responsible for bacterial diarrhea in neonatal piglets. The susceptibility of piglets to ETEC F4ac is determined by a specific receptor on the small intestinal epithelium surface. We performed an iTRAQ-labeled quantitative proteome analysis using a case-control design, in which susceptible and resistant full-sib piglets were compared for the protein expression levels. 2249 proteins were identified, of which 245 were differentially expressed (fold change > 1.5, FDR-adjusted P < 0.05). The differentially expressed proteins fell into four functional classes: (I) cellular adhesion and binding, (II) metabolic process, (III) apoptosis and proliferation, and (IV) immune response. The integrin signaling pathway merited particular interest, based on a pathway analysis using statistical overexpression and enrichment tests. Genomic locations of the integrin family genes were determined based on the most recent porcine genome sequence assembly (Sscrofa11.1). Only one gene, ITGB5, which encodes the integrin β5 subunit that assorts with the αv subunit to generate integrin αvβ5, was located within the SSC13q41 region between 13:133161078 to 13:139609422, where strong associations of markers with the ETEC F4ac susceptibility were found in our previous GWAS results. To identify whether integrin αvβ5 is the ETEC F4acR, we established an experimental model for bacterial adhesion using IPEC-J2 cells. Then ITGB5 gene was knockout in IPEC-J2 cell lines using CRISPR/Cas9, resulting in a biallelic deletion cell line (ITGB5-/-). Disruption of ITGB5 significantly reduced ETEC F4ac adhesion to porcine intestinal epithelial cells. In contrast, overexpression of ITGB5 significantly enhanced the adhesion. GST pull-down assay with purified FaeG and ITGB5 also showed that FaeG binds directly to ITGB5. Together, the results suggest that ITGB5 is a key factor affecting the susceptibility of piglets to ETEC F4ac.